DOMINANT SPEECH ACT TYPE IN DAILY CONVERSATION: A PRAGMATIC STUDY - Syafryadin Syafryadin; Imam Sudarmaji; Santiana Santiana (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2022)
Speech act is an act of communication that must be understood by the speaker and listener. Misunderstanding of speech act in conversation or dialogue can cause the misleading in the conversation. Therefore, this study aims to analyze the speech act types in daily conversation between students and parents at home. Qualitative research design was undertaken by the researcher to gain the speech act types. The research participants were twenty-four students of English Education department. Checklist was used to obtain the data. Moreover, the data were analyzed by using qualitative analysis by applying several stages from reduction, displaying and drawing conclusion. The result showed that several types of speech were found during conversation of students and parents at home. Those were directive, declarative, expressive and commissive. The dominant speech act type was directive because the parents asked the students to do something at home. Another finding showed that the students and parents did not use representative speech act in the conversation. It is because in the conversation between students and parents at home were informal conversation that seldom or never use representative. In short, it is not all speech appeared in the conversation because it depends on the function of speech act itself.